Minutes of the 19th meeting of BRAC University academic council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
Minutes of the 19th Meeting of BRAC University Academic Council, held on Sunday, 18th December, 2005.